Evaluasi Hasil Inspeksi Alat Pemadam Api Ringan Berdasarkan Peraturan Menteri Tenaga Kerja dan Transmigrasi No. 4 Tahun 1998 di Pabrik Susu - Moch Luqman Ashari; Muhammad Daffa Rabbani; Arya Kusuma Wijaya; Moch Akbar Ilhami Septiansyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Dairy is an industry in the food manufacturing sector that has priority for development in Indonesia. To maintain its quality, implementing health safety management as a standard operating procedure to create a safe and healthy company work environment. To create a safe and healthy work environment, all areas of the Dairy Company have been equipped with an active factory fire protection system, namely Light Fire Extinguishers (Fire Extinguisher). Even though the potential fire hazard rarely occurs in this company, Fire Extinguisher inspections within this company must still be carried out regularly to minimize the impact of a fire that might occur. The purpose of this study is to identify potential hazards and assess current fire extinguisher inspection procedures using observation methods and secondary data from documents and other archives. The results of this study indicate that the company has implemented safety and health management as evidenced by the company's regular inspections of fire extinguishers. From the results of examining these variables, which are in accordance with the Regulation of the Minister of Manpower and Transmigration No. 4 of 1998 is the maintenance of Fire Extinguisher which covers the condition of the pressure of the contents of the tube, seals, nozzle nozzle, installation, and condition of the Fire Extinguisher tube. The conclusion from this research is that the Dairy Factory has carried out inspections in accordance with the Regulation of the Minister of Manpower and Transmigration No. 4 of 1998.